FORMATION OF MUSICAL THINKING IN YOUTH THROUGH KNOWLEDGE OF SONG GENRES AND FORMS (Innovate Conferences, 2025)
This article emphasizes the importance of musical education in nurturing a well-rounded personality. Folk oral creativity is considered a profound spiritual wealth of every nation. Within the oral musical tradition, the continuity of performance practices has been preserved and developed largely through the master–apprentice relationship. The paper also discusses the role of popular music in contemporary world culture and highlights how the invention of mass media—such as radio, television, sound recording, and distribution technologies like the gramophone and tape recorder—has significantly contributed to the global dissemination of musical traditions.